The Genetic Counselor: Responsible to Whom? (The Hastings Center report, 1971)
When Marc Lappé recently joined the staff of the Hastings Center as Associate for the Biological Sciences, he circulated these preliminary thoughts on ethics and genetic counseling for staff discussion. They were not intended for publication. But since the issues touched upon are fundamental, Dr. Lappé's permission was received to publish his letter, along with the comments of some of his colleagues at the Center. We invite readers to join the discussion, in the correspondence section beginning in the next issue of Report.